2018
DOI: 10.3989/mc.2018.01817
|View full text |Cite
|
Sign up to set email alerts
|

Defect characterization, diagnosis and repair of wood flooring based on a field survey

Abstract: A statistical characterization of defects in 35 buildings and 98 wood floorings (softwood and hardwood floors, and laminated and engineered wood floors), their diagnostic methods and repair solutions is presented. An expert system for inspecting wood flooring, comprising the classification of defects, their most probable causes, diagnostic methods and repair techniques, was used. Results include age, affected area, severity and frequency of defects and their main causes, as well as appropriate diagnostic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Comparing the incidence of anomalies in VLF with that of wood floorings, it is found that, in wood floorings, scratches, or wrinkles (above 80% of floorings) are also the most common detected anomaly [33]. In wood floorings, scratches are even more predominant, as the next frequent anomaly is only detected in about 25% of inspected floorings.…”
Section: Anomalies Observed In the Samplementioning
confidence: 96%
See 3 more Smart Citations
“…Comparing the incidence of anomalies in VLF with that of wood floorings, it is found that, in wood floorings, scratches, or wrinkles (above 80% of floorings) are also the most common detected anomaly [33]. In wood floorings, scratches are even more predominant, as the next frequent anomaly is only detected in about 25% of inspected floorings.…”
Section: Anomalies Observed In the Samplementioning
confidence: 96%
“…furniture without adequate protections. In wood floorings [33], the circulation on floorings is also identified in all scratch's anomalies.…”
Section: Probable Causes Of Anomaliesmentioning
confidence: 96%
See 2 more Smart Citations
“…Propusieron un sistema de apoyo a la inspección y diagnóstico que caracterizaba la situación patológica de cada elemento inspeccionado, facilitando la sistematización de las inspecciones incluidas en las actuaciones de mantenimiento periódico y evitando así futuros defectos. Este enfoque, centrándolo en los revestimientos de suelos de madera, ha sido recientemente aplicado por el departamento de ingeniería civil de la Universidad de Lisboa, en una muestra de 35 edificios (19), y también, al estudio de la variabilidad de pruebas in situ destinadas a conocer el envejecimiento natural de revestimientos de paredes enlucidas (20).…”
Section: Introductionunclassified